2005
DOI: 10.1002/asna.200410394
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between penumbral intensity and flow filaments

Abstract: Abstract. Taking advantage of high spatial (≈ 0.5 arcsec) and high spectral (λ/δλ = 250 000) resolution observations obtained with the 2D spectrometer TESOS, we analyze a sunspot located at a heliocentric angle of 23• . We elaborate on the issue of a correlation between dark filaments and the Evershed flow in sunspot penumbrae. Controversies on the existence of such a correlation are resolved: It varies from the inner to the outer penumbra, from the center-side to the limb-side penumbra, and depends on the len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
5
18
0
Order By: Relevance
“…The curves depicted in Fig. 14 reveal that larger continuum intensities are associated with larger LOS velocities, i.e., the Evershed flow is more intense in the brighter structures, at least in the inner center-side penumbra. This agrees with the conclusions of Bello González et al (2005) and Schlichenmaier et al (2005).…”
Section: Do We See Individual Flow Channels?supporting
confidence: 94%
“…The curves depicted in Fig. 14 reveal that larger continuum intensities are associated with larger LOS velocities, i.e., the Evershed flow is more intense in the brighter structures, at least in the inner center-side penumbra. This agrees with the conclusions of Bello González et al (2005) and Schlichenmaier et al (2005).…”
Section: Do We See Individual Flow Channels?supporting
confidence: 94%
“…These properties can change with radial distance. For example, Schlichenmaier et al (2005) suggested that flow filaments link bright and dark continuum features at different radial distances. Since ECs move along intra-spines (i.e., flow filaments), we may expect them to be associated with locally bright features in the inner penumbra.…”
Section: Comparison Of Line Parameters In Ecs and Intra-spinesmentioning
confidence: 99%
“…As mentioned in the introduction, the Evershed flow is observed to be directed along the more inclined intra-spines, which coincide with dark filaments in the outer penumbra and bright filaments in the inner penumbra Schlichenmaier et al 2005;Bellot Rubio et al 2006;Ichimoto et al 2007). Since dark material usually means cooler and therefore more neutral plasma, the conjecture is that neutral iron lines mainly form in dark filaments (those harboring Evershed flow in the outer penumbra) and ionized iron lines form in the hotter and brighter filaments with stronger and more vertical fields.…”
Section: Discussion Of the Results And Uncertaintiesmentioning
confidence: 62%
“…The relation between the brightness of penumbral filaments and the Evershed flow is not straightforward. There are indications that the more horizontal component of intraspines coincides with dark filaments in the outer penumbra and with bright ones in the inner penumbra (Schlichenmaier et al 2005;Bellot Rubio et al 2006;Ichimoto et al 2007). Up-and downflows are superimposed on the radial outflow and produce a difference in the velocity inclination angle between the bright and dark features depending on the radial distance in the penumbra .…”
Section: Introductionmentioning
confidence: 97%